Detection and Characterization of BCR-ABL Transcripts in Bangladeshi CML Patients by Cost Effective RT-PCR - Soad, Md. Shahjalal; Akhter, Khadiza; Shekhar, Hossain Uddin (ABC Journal of Advanced Research, 2016)
Philadelphia (Ph) chromosome or the BCR-ABL fusion gene is used to diagnose, determine treatment strategy of chronic myelogenic leukemia (CML) and acute lymphoblastic leukemia (ALL). The fusion gene transcript may vary depending on the reciprocal translocation between chromosome 9 and 22. Hence, identification and characterization of the BCR-ABL transcripts are important for the treatment and management of leukemia patients. In this study, a primer set and clinical molecular diagnosis assay were established to identify the BCR-ABL transcripts by conventional polymerase chain reaction (PCR). A parallel analysis was done for quantitative real-time polymerase chain reaction (Q-PCR) and conventional PCR. This study is based on reverse transcriptase PCR (RT-PCR) of 87 CML patients’ RNA to generate total cDNAs and the selection of the BCR-ABL transcripts by conventional polymerase chain reaction using specific primer set. A BCR primer BCR-e12: GCAGAGTGGAGGGAGAACAT and a reverse ABL primer ABL-a3: GCTTCACACCATTCCCCATT was established to select three different Philadelphia major transcripts (b3a2, b2a2 and b3a3). Sixty-one Philadelphia positive samples (35 b3a2, 22 b2a2 and 4 b3a3 fragments) were detected out of 87 CML patients. Q-RT-PCR was then performed, and ten discrepancies were found in the study. Four samples found positive in conventional PCR resulted negative in Q-PCR and other six samples (positive in Q-PCR) gave the negative result in conventional PCR. Though Q-PCR is quantitative and highly specific, it is expensive and can’t characterize BCR-ABL fragments. On the other hand, conventional PCR is less reliable but is inexpensive and helpful for characterization of the target fusion gene. Performing both Q-PCR and conventional PCR can detect each and every positive case of CML as well as give no false positive or false negative result.